The antecedents and influence of consumer relationship proneness towards perceived relationship quality and customer loyalty of apparel retailing industry in Malaysia / Siti Ilmiah Ismail - Ismail, Siti Ilmiah (2014)
Relationship marketing has been proven to have a positive influence on customer loyalty. However, relationship marketing practices itself is not enough in developing customer loyalty without targeting the program to the right customers who are prone to relationship. Retailers need to consider the individual differences, including the consumer’s feelings about relationship marketing efforts. So, this study will investigate whether consumer relationship proneness (CRP) has a positive influence towards relationship quality and customer loyalty in apparel retailing industry. Although there are various studies investigating the importance of CRP in retail industry context, there are limited studies dealing with the antecedents of CRP. A conceptual framework has been developed to indicate that CRP is influenced by two dimensions of shopping orientation which is fashion consciousness and price consciousness as well as CRP that influenced relationship quality and customer loyalty. Data will be collected using mall intercept survey with systematic sampling of apparel retailer’s consumers in Malaysia. It is important for retailers to understand that perspective because they can target the relationship marketing effort to the right customers. The retailer seeks understanding on what factors can influence CRP so that they can influence it over time. This paper is the first to explore the fashion consciousness and price consciousness as antecedents of CRP.